ANALISIS PENGARUH LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP RETURN SAHAM (Studi Pada Perusahaan Manufaktur di BEI) Periode 2011-2013 - Vivin Serpentina Honifera, 11.05.51.0121 (Students Journal of Economic and Management, 2015)
This study aimed to examine the effect of liquidity , solvency , and profitability of the Stock Return. Sample using purposive sampling method with criteria manufacturing company that has complete data for the population and the company for 3 years ( 2011-2013 ) obtained 240 samples .Analysis techniques using multiple linear regression method previously normality test , the classical assumption includes multicollinearity , autocorrelation , and heteroscedasticity . In addition , this study also uses statistical test t and F as well as the coefficient of determination . The test results normal distribution of data , and all the classical assumptions are met .The results showed that the liquidity and solvency has no effect on stock returns . While profitability and significant positive effect on stock returns .Keywords : Liquidity , Solvency and Stock Return .